Peningkatan keterampilan menulis narasi melalui model pembelajaran cooperative integrated reading and composition pada mata pelajaran bahasa indonesia - Aji, Wahyu Sulistyo; Sriyanto, Muhammad Ismail; Chumdari, Chumdari (Didaktika Dwija Indria, 2019)
The purpose of this research is to improve narrative writing skill through Cooperative Integrated Reading and Composition (CIRC) learning model on students fifth class of Laweyan No. 54 Surakarta Public Elementary School academic year 2018/2019. The form of  research is a classroom action research, conducted for two cycles with the planning, implementation, observation, and reflection on each cycle. Data collection techniques are using interviews, observations, tests, and documentation. Data validity technique is using triangulation. Data analysis techniques is interactive analysis  model that includes data reduction, data display, and conclusion rawing verification. The result of research showed that using CIRC learning model can improve narrative writing skill. The average score of each aspect of the students' narrative writing skills has increased, from 11.47 at the pretest, then after the action by applying CIRC to 13.56 in the first cycle, 80.11 in the second cycle and including the skilled category. The conclusion of this research is the narrative writing skills of fifth grade students of Public Elementary School Laweyan No. 54 Surakarta academic year 2018/2019 increases through the application of Cooperative Integrated Reading and Composition (CIRC) learning models.Keywords: Narrative text, writing skill, Cooperative Integrated Reading and Composition (CIRC).